Са2+-permeable cation channels of the plasma membrane of higher plant cells - Mackievic, Viera S.; Samokhina, Veranika V.; Hryvusevich, Palina V.; Vaitsiakhovich, Maryia A.; Sokolik, Anatoly I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
Calcium (Ca2+ ) is an important structural element, regulator of metabolic processes and ubiquitous for all living systems signaling agent that provides a link between membrane receptors and gene expression. The most significant phenomenon determining the signal-regulatory function of Ca2+ is its transport through the plasma membrane and the endomembranes of the cell. A key role in this processes is played by cation channels localized in all membranes of the plant cell. Bioinformatics analysis of plant cation channels has not revealed the presence of Ca2+-selective filters similar to the systems found in animals. However, plant membranes show pronounced Ca2+-mediated currents, i. e. exhibit high permeability to Ca2+. Biophysical characteristics of plant Ca2+ conductances has recently been studied in details and supplemented by molecular analysis. Ca2+ conductance in plant cell membranes is mediated by different cation channelsencoded by several families of ion channel genes, such as «cyclic nucleotide-gated channels» (CNGCs), «ionotropic glutamate receptors» (GLRs), «two-pore channel 1» (TPC1), «annexins» and «mechanosensitive-like channels» and some others. Recent studies also suggest that perception of external environmental factors, such as salinity, temperature, pH, gravity, mechanical stimulation, chemical agents, phytohormones and others is associated with the activity of specific subunits of these ion channels.
Keywords: calcium; cation channels; Ca2 conductance; cyclic nucleotide-gated channels; ionotropic glutamate receptors; mechanosensitive channels; higher plants